Chhattisgarh community mental healthcare tele-mentoring program (CHaMP): Digitally driven initiative to reach the unreached. (August 2022) - Ibrahim, Ferose Azeez; Malathesh, Barikar C; Gajera, Gopi; Pandey, Praveen; Nirisha P, Lakshmi; Jyrwa, Sonakshi; Kumar, Channaveerachari Naveen; Manjunatha, Narayana; Jain, Sumi; Bairy, Bhavya K; Bada Math, Suresh
Objective: Harnessing technology is one accepted method to leapfrog the barrier of inadequate trained human resources for mental health. The Chhattisgarh Community Mental Healthcare Tele-Mentoring Program (CHaMP) is a collaborative digitally driven initiative of the Government of Chhattisgarh (GOC) and the National Institute of Mental Health and Neuro Sciences (NIMHANS), Bengaluru the aim of which is to train the Primary Care Doctors (PCDs) and Rural Medical Assistants (RMA) to identify, screen and treat/refer cases of mental health disorders presenting to the primary care settings ( n = 2150). The objective of this article is to give a brief overview of the initiative Methods: CHaMP consists of the following modules: (a) a brief on-site training (b) eLearning and Skill Development (eLSD) and (c) Collaborative Video Consultation (CVC). The latter two are andragogic training methods delivered digitally. Results and conclusion: From August 2019 to May 2020, 501 PCDs and RMAs have been covered. During this time, they have cared 15, 000 patients suffering from mental illness, which hitherto was not the case. Technology that is easily available and usable has the potential to overcome the big hurdle of inadequate mental health human resources in India.